Petisi Online Sebagai Media Advokasi Alternatif dalam Upstream Social Marketing - Nia Ashton Destrity (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2018)
Social marketing as a method encourages behavioral change in individuals for a better life by adopting concepts and principles in commercial marketing. Changes of individual behavior are influenced by social contexts that cannot be separated from the role of the upstream actors (parties who have influence in the policy-making process). In accordance, targeting upstream actors for social marketing activities has become a challenge. Therefore, social marketers need to communicate creatively with upstream parties to support their social marketing goals. This conceptual article aims to explain the importance of moving upstream as a concept and describes the use of online petitions as an alternative platform for media advocacy establishing an upstream social marketing strategy. It is argued that the development of information and communication technology offers an online petition platform for reaching upstream parties. Through a study of literature method, this article presents a case of online petition Change.org Indonesia which is supported by the media and policymakers. Change.org Indonesia has been actively developing media advocacy through the press conference, press release and press note, social media, and offline actions or events to influence policymakers in order to create a supportive environmental condition for behavioral change.